Benchmarking publication metrics for Indian business researchers: Exploring the role of collaboration. Issue 2 (25th October 2019) - Behl, Abhishek; Chavan, Meena; Dutta, Pankaj; Sheorey, Pratima Amol
Abstract : Purpose: There is no particularly efficient way to measure research output, but effectual assessment of research output is necessary to motivate and encourage researchers to enhance their research performance and disseminate knowledge. The purpose of this paper is to highlight the exacerbating pressure on Indian academics to deliver incessantly in terms of research output and identify an agreeable way to increase research output. The metric explores trends in management publications by Indian academics and presents an overview of collaborative practices by Indian management researchers that could shine a light on the trends of collaborative publishing future. Design/methodology/approach: The study focuses on publications in the area of Business and Management. Scopus was used with advanced filters to draw relevant research papers. Data were then sorted and filtered on the basis of quality determined through Australian Business Deans Council rankings and diverse bibliometric information to understand the pattern of research output of Indian academics. Findings: The research found that the rate of collaboration with researchers from the home country is low for top rated publications. Majority of publications were listed in Scopus indexed journals, whereas a handful featured in A and A* journals. A and A* journals were predominantly co-authored with academics from universities outside the country. Tradeoff was achieved by majority of authors by getting published in B, followed by C category journals to achieve research outputs. Research limitations/implications: The study is limited to publications in the area of Business and Management and may be extended to other disciplines such as economics, engineering, law, medical sciences, etc., to understand publishing trends at universities in the country. The study can also be conducted in understanding a similar dilemma with academics at other countries that are evolving in research culture. Practical implications: The study would help management researchers to dig deep into the root cause and understand why and how collaborations within and outside the country impact the quality of publications. The results would further encourage ranking agencies to award suitable grades to colleges that promote collaboration within the country as well as international collaboration. The study also conducts a benchmarking exercise of the institutions in the country that would be useful for researchers, journals and colleges. Originality/value: While earlier studies have highlighted the importance of foreign collaborations in academic publishing, there are a handful of studies that have focused on the role of collaboration within the home country. The practice of Indian authors collaborating with Indian counterparts at other universities would help understand the expertise of researchers at different universities and encourage the collaboration process and quality of publications in the country.